2014
DOI: 10.4209/aaqr.2013.05.0174
|View full text |Cite
|
Sign up to set email alerts
|

Source Profiles of Volatile Organic Compounds from Biomass Burning in Yangtze River Delta, China

Abstract: The volatile organic compounds (VOCs) associated with biomass burning were characterized in the Yangtze River Delta of China, including two types of burning conditions (stove burning and field burning) and five typical kinds of biomass (straws of rice, wheat, bean and rape, and wood). According to the results, the VOC emission factors of straw burning ranged from 2.08 g/kg to 6.99 g/kg with an average of (4.89 ± 1.70) g/kg, compared to 0.98 g/kg for wood burning. Some differences in VOC composition were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 20 publications
2
35
2
Order By: Relevance
“…Six different concentrations of a standard sample (0.03–0.25 ppbv) were used to calibrate the GC‐MS/FID every 2 weeks. Further details about the detection limits and the quality assurance/quality control of this instrument can be found in Wang et al [] and X. P. Lyu et al [].…”
Section: Methodsmentioning
confidence: 99%
“…Six different concentrations of a standard sample (0.03–0.25 ppbv) were used to calibrate the GC‐MS/FID every 2 weeks. Further details about the detection limits and the quality assurance/quality control of this instrument can be found in Wang et al [] and X. P. Lyu et al [].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, biomass and biofuel burning could contribute up to 70 % of the global secondary organic aerosol (SOA) burden (Shrivastava et al, 2015) and hence influence the seasonal variation of global SOA (Tsigaridis et al, 2014). Since it produces large amounts of primary and secondary pollutants, it is essential to characterize primary emissions and photochemical evolution of biomass burning in order to better understand its impacts on air quality (Huang et al, 2014), human health (Alves et al, 2015) and climate change (Andreae et al, 2004;Koren et al, 2004;Laskin et al, 2015;.…”
Section: Z Fang Et Al: Open Burning Of Rice Corn and Wheat Strawsmentioning
confidence: 99%
“…Volatile organic compounds (VOC) have been known to cause both acute and chronic health effects, especially on the respiratory system. Numerous studies indicated that various VOC species are emitted from agriculture residue burning [4][5][6].…”
Section: Introductionmentioning
confidence: 99%